Seasonal changes in microbial community composition in river water studied using 454-pyrosequencing - Kaevska, Marija; Videnska, Petra; Sedlar, Karel; Slana, Iva (SpringerPlus, 2016)
The aims of this study were to determine the microbial community in five rivers in the proximity of a city in the Czech Republic using 454-pyrosequencing, as well as to assess seasonal variability over the course of 1 year and to identify the factors influencing the structure of bacterial communities. Samples from five rivers around the city of Brno were obtained during four seasons and analysed using 454 pyrosequencing of the 16S rRNA gene. The core composition of bacterial communities consisted of Actinobacteria, Bacteroidetes, Proteobacteria, Firmicutes, Fusobacteria, TM7 and others. Our approach enabled us to more closely study the correlation between the abundance of different families and environmental factors. Overall, Actinobacteria negatively correlated with phosphorus, sulphate, dissolved particle and chloride levels. In contrast, Proteobacteria positively correlated with sulphate, dissolved particle, chloride, dissolved oxygen and nitrite levels. Future work should focus on the dynamics of bacterial communities present in river water and their relation to the overall stability of the water ecosystem.
Keywords: Microbial community; Environmental factors; Pyrosequencing; River water